Stigmatization Towards Healthcare Workers During the COVID-19 Pandemic in Nepal - Nepal, Richa; Pradhan, Ravi Ranjan (Nepalese Medical Journal, 2020)
COVID-19 is a novel disease that accompanies itself with anxiety, fear and social stigma. As the numbers of COVID-19 cases continue to rise in Nepal, many instances of stigmatization towards healthcare workers have come into light. Rather than motivating healthcare workers to work during these adverse times, they are being ostracized as carriers of COVID-19. Despite the risks, healthcare workers are bearing for themselves and for their families, very little has been done to protect them. Stigmas can be counteracted by awareness regarding this novel disease. It is important to aware people about correct practices and makes them realize that this battle against COVID-19, can’t be won without healthcare workers. Ensuring safety of healthcare workers must be the foremost priority of the state. Healthcare workers are the most valuable asset for every country, who must be protected from acts of stigmatization at the earliest.